Contrary to expectation: Preserved renal function after using PD-1 Inhibitor Cemiplimab-rwlc in a kidney transplant recipient - Muhannad Leghrouz; Svetomir N Markovic; Aleksandra Kukla (Archives of Organ Transplantation - Peertechz Publications, 2022)
The use of immune checkpoint inhibitors in transplant recipients with malignancy is associated with the risk of graft failure due to acute rejection. There is limited literature regarding the use of Cemiplimab-rwlc (Libtayo) in kidney transplant patients. Here we present a case of using Cemiplimab-rwlc (Libtayo), a Programmed Death receptor-1 (PD-1) blocking antibody for locally advanced and metastatic Cutaneous Squamous Cell Carcinoma (CSCC), in a kidney transplant recipient.